2018
DOI: 10.1093/brain/awy222
|View full text |Cite
|
Sign up to set email alerts
|

Basal ganglia and cerebellar pathology in X-linked dystonia-parkinsonism

Abstract: X-linked dystonia-parkinsonism is a neurodegenerative movement disorder characterized by adult-onset dystonia combined with parkinsonism over the disease course. Previous imaging and pathological findings indicate exclusive striatal atrophy with predominant pathology of the striosomal compartment in the dystonic phase of X-linked dystonia-parkinsonism. The striosome occupies 10-15% of the entire striatal volume and the density of striosomes follows a rostrocaudal gradient with the rostral striatum being consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
74
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(87 citation statements)
references
References 74 publications
12
74
1
Order By: Relevance
“…One study proposed that transcriptional interference due to G-quadruplex formation might be one of the primary processes influencing the disease manifestation. [27][28][29] In conclusion, our study confirms that approximately half of the AAO difference in the XDP patient population can be explained by the (CCCTCT) n repeat element. 23 Instead, multiple loss-and gain-of-function mechanisms act in concert to fuel neurodegeneration.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…One study proposed that transcriptional interference due to G-quadruplex formation might be one of the primary processes influencing the disease manifestation. [27][28][29] In conclusion, our study confirms that approximately half of the AAO difference in the XDP patient population can be explained by the (CCCTCT) n repeat element. 23 Instead, multiple loss-and gain-of-function mechanisms act in concert to fuel neurodegeneration.…”
Section: Discussionsupporting
confidence: 79%
“…Finally, further variability may be explained by interindividual differences of the brain to compensate for the advanced neurodegenerative changes that can be observed already in early disease stages. [27][28][29] In conclusion, our study confirms that approximately half of the AAO difference in the XDP patient population can be explained by the (CCCTCT) n repeat element. It also revealed a positive correlation with disease severity and cognitive dysfunction in XDP and an inverse correlation with TAF1 expression.…”
Section: Discussionsupporting
confidence: 79%
“…Available data were insufficient for a meta-analysis in cases of DYT/PARK- TAF1 , associated with X-linked dystonia-parkinsonism (XDP or Lubag disease)30; DYT- SGCE , responsible for an early-onset form of myoclonus-dystonia predominantly involving the neck and arms3; CHOR/DYT- ADCY5 , which may cause a variable phenotype characterised by chorea, dystonia or myoclonus31 32; GNAO1 , associated with a form of childhood dystonia combined with other hyperkinetic movement disorders, cognitive impairment and seizures33; and ACTB , responsible for a clinical phenotype characterised by dystonia and deafness 34 35. However, outcomes may not be significantly different from those observed in DYT- TOR1A using age- and disease-duration-adjusted motor and disability outcomes, with the only exception of CHOR/DYT- ADCY5 that showed significantly lower benefits from GPi DBS than DYT- TOR1A .…”
Section: Discussionmentioning
confidence: 99%
“…While these outcomes are encouraging, it is important to note that the clinical picture associated with DYT/PARK- TAF1 (ie, XDP) may change over time. Focal dystonia tends to generalise within the first 5 years; after 10 years, dystonia becomes relatively less severe in the face of increasingly prominent parkinsonian signs 30. A recent observational study from 16 patients showed that GPi DBS may also improve the parkinsonian features associated with XDP 36.…”
Section: Discussionmentioning
confidence: 99%
“…3 Postmortem investigations identified a loss of striatal medium spiny neurons predominantly in the striosomal compartment, which resulted in striking striatal atrophy. [4][5][6][7] Dystonia in XDP is severe and results in immobility, pain, insufficient food intake, weight loss, and aspiration, and oral treatments with antidystonic drugs are largely ineffective. 8 Deep brain stimulation of the internal pallidum (GPi-DBS) is an established therapeutic option in patients with treatment-refractory generalized and segmental-isolated dystonia 9 and has successfully been used in individual patients with XDP, providing anecdotal evidence only.…”
mentioning
confidence: 99%